Prevalence of Prohibited Substance Use and Methods by Female Athletes: Evidence of Gender-Related Differences - Collomp, Katia; Ericsson, Magnus; Bernier, Nathan; Buisson, Corinne (Frontiers in Sports and Active Living, 2022)
To achieve optimal sports performances, women and men may show specific doping practices due to physiological and psychological sex differences, but there are few data on this topic. Here, we report the apparent use of prohibited substances and methods by female athletes based on analyses of the doping tests collected by the French Anti-Doping Agency from 2013 to 2019. We compared the frequency of use and the ergogenic and side effects to those of their male counterparts. The results revealed lower use of prohibited substances in female vs. male athletes, with significantly fewer anabolic agents, hormone and metabolic modulators, and cannabinoids. Sex specificity in utilization of substance classes was also shown. Relatively lower use of hormone modulators and cannabinoids and higher use of beta-2 agonists, diuretics and glucocorticoids were found in the female cohort compared to males, combined with the different choice of substances, possibly because of altered ergogenic and/or side effects. However, no sex impact regarding the sports disciplines was observed, with both females and males showing similar use of anabolic agents, mainly in anaerobic sports, and EPO and corticoids, mainly in endurance or mixed sports. Further studies are needed to put these French data into a global perspective, comparing uses across countries and exploring possible new developments in the fight against doping in women.